2016
DOI: 10.1002/ange.201511678
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism of the First Carbon–Carbon Bond and the First Olefin in the Methanol Conversion into Hydrocarbons

Abstract: In dieser Zuschrift wurde fälschlicherweise eine in der Literatur angegebene Reakti-onsgeschwindigkeit als Geschwindigkeitskonstante bei der Geschwindigkeitsberech-nung in den Hintergrundinformationen (S9) verwendet:"As emi-quantitative estimation of the carbonylation rate is made based on reported kinetic data from literature. A rate constant of 6.8 mol (g atom Al) À1 h À1 was applied for the reaction on HZSM-5 at 450 8 8C, according to literature (Fig. 1Angew.C hem. Int. Ed. 2006, 45, 1617-1620). Applying ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…Recently, we observed that higher temperatures are required to desorb DME in comparison to methanol providing evidence that DME stays longer on the catalysts and is the key oxygenate. This was also evidenced by Liu et al and Wei et al . In this paper, we investigate the induction period during the formation of primary olefins from DME at 300°C by conducting novel step response experiments in a temporal analysis of products (TAP) reactor.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Recently, we observed that higher temperatures are required to desorb DME in comparison to methanol providing evidence that DME stays longer on the catalysts and is the key oxygenate. This was also evidenced by Liu et al and Wei et al . In this paper, we investigate the induction period during the formation of primary olefins from DME at 300°C by conducting novel step response experiments in a temporal analysis of products (TAP) reactor.…”
Section: Introductionmentioning
confidence: 57%
“…Various direct mechanisms have been proposed for the conversion of methanol/DME to primary olefins . These direct mechanisms are known by their intermediates and include oxonium ylide, carbene, methane‐formaldehyde, carbon monoxide, methoxymethyl, and surface methoxy groups . Using density functional theory (DFT) calculations, Lesthaeghe et al refuted some direct mechanisms based on high activation energy barriers and highly unstable intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations